Open Education and the Sustainable Development Goals: Making Change Happen - Andy Lane (Commonwealth of Learning, 2017)
Education for All has been a concept at the heart of international development since 1990 and has found its latest instantiation within the Sustainable Development Goals (SDGs) as SDG 4, ‘Ensure inclusive and equitable quality education and promote lifelong learning opportunities for all’. Open education, in the form of resources and practices are both seen as contributors to SDG4 as evidenced by the recent 2nd World Open Educational Resources Congress. The ambition for open education to contribute to the SDGs is clear from this and other gatherings but the means to make it happen are not as clear, and many have claimed that little has happened since the SDGs were launched in 2015. To help address this apparent gap, this paper: (1) sets out the scale and scope of the SDGs; (2) reviews the potential contribution of open educational resources and practices to support the SDGs, and (3) uses a framing of power and systems thinking to review the way open education activities might be fostered within tertiary education in all local, national and regional contexts in order to support the SDGs, and not just SDG 4. It will also tentatively propose a theory of change that brings together power relationships, systems thinking and open education as key components and provide a case study of how this might work in practice through a newly funded project proposal. It is hoped that this theory of change and proposal will be a starting point for wider debate and discussion on how to make change happen in this important arena.